Gender and recovery from coronary artery bypass surgery : a psychological perspective - Kendel, Friederike (Springer, 2017)
The number of coronary artery bypass graft (CABG) operations has increased continually over the past decade. To date, roughly one-third of these are performed on women. Despite the tremendous progress made in cardiovascular surgery, not all patients profit equally from it, and the mortality rate of women still exceeds that of men by a factor of two. Studies conducted to investigate this marked gender difference have yielded conflicting results. In particular, adjustment for clinical risk factors seemed to diminish the difference, but could not fully explain it.